Efectos del nivel socioeconómico de la zona de residencia sobre el proceso de estratificación social en Monterrey - Solís, Patricio; Puga, Ismael (El Colegio de México A.C., 2011)
This study explores the effects of the socio-economic composition of the areas of residence on the process of social stratification in the city of Monterrey. On the basis of a modified version of the classical model of achievement of status proposed by Blau and Duncan, we use multilevel, linear regression and time models to test some hypotheses on the effects of socio-economic level on zone of residence in eight educational and occupational results: completed years of schooling; leaving school; first job; occupation at age 21 (or first job if the person entered the labor force later); leaving a job and changing jobs to highly skilled non-manual occupations, unskilled non-manual work and manual work. The effects are significant in five of these eight results, suggesting that the socio-economic level of the zone of residence plays a key role as a determinant in a person’s educational and occupational career throughout their lives.